2013
DOI: 10.3892/mmr.2013.1822
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ginsenoside Rg1 on lidocaine-induced apoptosis

Abstract: Lidocaine, as an anesthetic substance, is often used for surface and spinal anesthesia. However, studies have shown that lidocaine may induce transient neurological symptoms and cauda equina syndrome. In the present study the effects of the ginsenoside Rg1 (Rg1) on lidocaine-induced apoptosis were assessed in Jurkat cells using flow cytometry and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL). The data showed that incubation with Rg1 provides protection against lidocaine-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…To date, more than 30 kinds of ginsenosides have been identified [9]. Ginsenoside Rb1 (G-Rb1) (the major pharmacological extract and chemical structure is shown in Figure 1) possesses a variety of biological activities in the cardiovascular systems probably through antioxidant, anti-inflammatory, and antiapoptosis [10], promoting angiogenesis [11] and an antiarrhythmic effect [12], suppressing ventricular remodeling after acute MI [13], and inhibiting hypertrophy and ventricular hypertrophy [14]. However, the efficacy and mechanisms of G-Rb1 for experimental MI have not been systematically evaluated yet.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 30 kinds of ginsenosides have been identified [9]. Ginsenoside Rb1 (G-Rb1) (the major pharmacological extract and chemical structure is shown in Figure 1) possesses a variety of biological activities in the cardiovascular systems probably through antioxidant, anti-inflammatory, and antiapoptosis [10], promoting angiogenesis [11] and an antiarrhythmic effect [12], suppressing ventricular remodeling after acute MI [13], and inhibiting hypertrophy and ventricular hypertrophy [14]. However, the efficacy and mechanisms of G-Rb1 for experimental MI have not been systematically evaluated yet.…”
Section: Introductionmentioning
confidence: 99%
“…As a herbaceous plant belonging to family Araliaceae, ginseng has been used as a drug in Asia and other regions for over 2000 years [ 16 , 17 ]. In recent years, more than 50 kinds of ginsenosides have been found, amongst which ginsenoside Rg3 (SPG-Rg3), as the active ingredient extracted from ginseng, is found to play an active role in the treatment of clinical diseases in recent studies [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-component treatments, characterized by two or more agents interacting with multiple targets simultaneously, are considered to be a rational and efficient form of therapy that is designed to control complex diseases (22,23), including stroke, which is a more complex disease than initially anticipated. Our previous study and those of others have already demonstrated that multi-component prescription (Tongluo Jiunao injection), composed of ginsenoside and ginsenoside Rg1 is effective for the treatment of stroke due to its anti-inflammatory, neuronprotecive and neurotrophic roles (19,24). The present study aimed to elucidate the synergistic effects of microglial cell-conditioned media treated with geniposide and ginsenoside Rg1 on hypoxia-injured neurons.…”
Section: Discussionmentioning
confidence: 87%